2002
DOI: 10.1074/jbc.m201943200
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Free Apolipoprotein E Binds to the Class B Type I Scavenger Receptor I (SR-BI) and Enhances Cholesteryl Ester Uptake from Lipoproteins

Abstract: The Class B type I scavenger receptor I (SR-BI) is a physiologically relevant high density lipoprotein (HDL) receptor that can mediate selective cholesteryl ester (CE) uptake by cells. Direct interaction of apolipoprotein E (apoE) with this receptor has never been demonstrated, and its implication in CE uptake is still controversial. By using a human adrenal cell line (NCI-H295R), we have addressed the role of apoE in binding to SR-BI and in selective CE uptake from lipoproteins to cells. This cell line does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
37
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 63 publications
(60 reference statements)
3
37
1
Order By: Relevance
“…However, the apoA-I-containing particles were better in inducing CE selective uptake. Other studies have confirmed that apoE is a ligand for SR-BI (57)(58)(59) and that the N-terminal region of apoE is involved in the binding to SR-BI (57 Westhuyzen showed that adenoviral overexpression of SR-BI in apoE-deficient mice resulted in only a modest depletion of LDL cholesterol levels, whereas no effect on VLDL cholesterol levels was observed (24). These studies might indicate that apoE on b-VLDL is important for recognition by SR-BI.…”
Section: Discussionmentioning
confidence: 94%
“…However, the apoA-I-containing particles were better in inducing CE selective uptake. Other studies have confirmed that apoE is a ligand for SR-BI (57)(58)(59) and that the N-terminal region of apoE is involved in the binding to SR-BI (57 Westhuyzen showed that adenoviral overexpression of SR-BI in apoE-deficient mice resulted in only a modest depletion of LDL cholesterol levels, whereas no effect on VLDL cholesterol levels was observed (24). These studies might indicate that apoE on b-VLDL is important for recognition by SR-BI.…”
Section: Discussionmentioning
confidence: 94%
“…It was the first authentic HDL binding protein to be characterized [51], although other ligands including apoE are now recognized [52]. A splice variant, termed SR-BII, was subsequently identified; this results from exon 12 skipping [30,53] to produce a receptor with a different C-terminal cytoplasmic tail, but identical extracellular binding region, to that of SR-BI.…”
Section: Discussionmentioning
confidence: 99%
“…The major apolipoproteins from HDL [apolipoprotein A-I (apoA-I), apoA-II, and apoC-III] mediate the binding of HDL to SR-BI (2). Recently, it was shown that lipid-free apoE also binds to SR-BI and enhances CE uptake from lipoproteins (3). In addition to HDL, SR-BI was found to bind a broad spectrum of ligands, including maleylated BSA, anionic phospholipids (PLs), modified lipoproteins (acetylated LDL, oxidized LDL, and hypochlorite-modified LDL), and native lipoproteins (HDL, LDL, and VLDL) (4)(5)(6)(7).…”
mentioning
confidence: 99%